Pre-9/11 politics of Islamophobia and Hanif Kureishi’s The Black Album (1995) - Malik Haroon Afzal; Mohamad Rashidi Mohd Pakri; Nurul Farhana Low Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2021)
The rising tide of Islamophobia and the consequent acts of violence pertaining to it over the past couple of years, is inflicting misery on Muslims living across the globe. This situation calls for a clear understanding of the phenomenon of Islamophobia. Using the New Historicist approach, this paper embarks on reading Hanif Kureishi’s The Black Album (1995) in the backdrop of the politics of Islamophobia in the pre-9/11 context. It thus attempts to highlight the working of the West-driven anti-Muslim political and literary discourse prevalent during the pre-9/11, or post-Cold-War era. The application of Stephen Greenblatt’s thesis of power, subversion and containment enables us to examine the selected novel by situating it within the actual political discourse prevalent during the time of its production to examine its treatment of the Western political narrative of Islamophobia. The study finds that since the 1990s, the West has been relying heavily on the political discourse that intensifies the narrative of Islamophobia in order to contain the subversion it encountered in the form of rising Muslim influence and immigration crises in the West. In the case of literary discourse however, we suggest that while The Black Album (1995) may seem to comply to the Western narrative of Islamophobia, it also offers sights of subversion to the anti-Muslim narrative by exposing Western bias and racist tendencies; and, in return, it ultimately demands negotiation and change.